1988
DOI: 10.1039/f29888401115
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour and lyotropic liquid crystals in cationic surfactant–water systems

Abstract: The sequence of lyotropic liquid-crystalline phases occurring in a range of cationic surfactants with water has been determined using the 'penetration' optical microscopy technique. Of the order of 50 different surfactants were examined. The variation of the polar group structure includes the series -NHl, -NMel, NEtl, NPrl and N B u~. In addition, the effect of altering counter-ion and alkyl-chain length are also examined. Other surfactants studied include 2-hydroxyethyl alkylammonium salts, nitroxide ring sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 3 publications
6
90
0
1
Order By: Relevance
“…Water solutions of CAT16 were prepared at a concentration of 2 mM and diluted as necessary. CAT16 micellar solutions possess a Kraft point of 313 K. 23 However, EPR analysis (Vide infra) showed that the solubilization of CAT16 micelles was more conveniently achieved at 333 K. Therefore, all solutions of CAT16, with and without n.5-SBDs, were prepared and stored at 333 K. Since aging of the samples stored at 333 K showed a progressive decrease in the EPR signal intensity, presumably due to a thermal degradation process, freshly prepared CAT16 solutions were used for all the EPR measurements that were performed at 333 K.…”
Section: Methodsmentioning
confidence: 99%
“…Water solutions of CAT16 were prepared at a concentration of 2 mM and diluted as necessary. CAT16 micellar solutions possess a Kraft point of 313 K. 23 However, EPR analysis (Vide infra) showed that the solubilization of CAT16 micelles was more conveniently achieved at 333 K. Therefore, all solutions of CAT16, with and without n.5-SBDs, were prepared and stored at 333 K. Since aging of the samples stored at 333 K showed a progressive decrease in the EPR signal intensity, presumably due to a thermal degradation process, freshly prepared CAT16 solutions were used for all the EPR measurements that were performed at 333 K.…”
Section: Methodsmentioning
confidence: 99%
“…Such phases are indeed known for divalent anionic, 29 zwitterionic, 30 non-ionic 31,32 and even mono-cationic surfactants with highly dissociated counterions (e.g. alkyltrimethylammonium chloride), 30 due to an increased effective area per headgroup a o .…”
Section: 28mentioning
confidence: 99%
“…alkyltrimethylammonium chloride), 30 due to an increased effective area per headgroup a o . Moreover, it should be noted that such cubic phases have also been identified in ternary or more complex mixtures of anionic surfactants.…”
Section: 28mentioning
confidence: 99%
“…59,60 The specific case of CTPA + , which is also precursor of a Pm n mesophase, will be discussed separately in a dedicated note in Sect. 3.4 because of its atypical micellar shape behaviour.…”
Section: Pm N Systemsmentioning
confidence: 99%